(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
The developed industry has an adverse effect on the ecological state of the environment, accompanied by the accumulation of harmful substances in the soil, including heavy metals. Therefore, the creation of technogenically resistant varieties of agricultural crops is one of the components of environmentally friendly technologies. This study is aimed at studying various genotypes of spring durum wheat for their resistance to the accumulation of cadmium and zinc in grain, which is a commercial part of the product. The content of the studied heavy metals in the soil of the root zone of various genotypes of spring durum wheat was investigated. The accumulation of the studied elements in seeds was determined, which is the most important studied indicator. The indices of productivity and survival of spring durum wheat genotypes were investigated in the field of natural pollution of the environment with heavy metals. The most stable and sensitive to the action of cadmium and zinc genotypes were revealed. The structure of spring wheat productivity from the collection and the relationship of its elements were analyzed. The identified resistant genotypes are recommended for further study of their productivity and survival in weather conditions of the East Kazakhstan region in field experiments to identify forms promising for agricultural production. Key words: cadmium, zinc, spring durum wheat.